2003
DOI: 10.1029/2002je002035
|View full text |Cite
|
Sign up to set email alerts
|

Rock size‐frequency distributions on Mars and implications for Mars Exploration Rover landing safety and operations

Abstract: [1] The cumulative fractional area covered by rocks versus diameter measured at the Pathfinder site was predicted by a rock distribution model that follows simple exponential functions that approach the total measured rock abundance (19%), with a steep decrease in rocks with increasing diameter. The distribution of rocks >1.5 m diameter visible in rare boulder fields also follows this steep decrease with increasing diameter. The effective thermal inertia of rock populations calculated from a simple empirical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
195
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(212 citation statements)
references
References 44 publications
17
195
0
Order By: Relevance
“…The lander is tolerant of rocks up to 45 cm high underneath a footpad, rocks up to 45 cm high underneath the lander bottom deck, and rocks up to 55 cm high underneath the deployed solar arrays and 10 cm less in all cases if excess energy is absorbed by crushable material inside the lander legs. If the rock sizefrequency distribution (SFD) is similar to models based on measured distributions at existing landing sites (e.g., Golombek and Rapp 1997;Golombek et al 2003bGolombek et al , 2008bGolombek et al , 2012b, then this translates to an overall rock-induced failure rate of ∼0.35 % in regions with a 5 % cumulative fractional area (CFA) and a failure rate of ∼2.5 % in regions with a 10 % CFA.…”
Section: Rock Abundancementioning
confidence: 99%
See 1 more Smart Citation
“…The lander is tolerant of rocks up to 45 cm high underneath a footpad, rocks up to 45 cm high underneath the lander bottom deck, and rocks up to 55 cm high underneath the deployed solar arrays and 10 cm less in all cases if excess energy is absorbed by crushable material inside the lander legs. If the rock sizefrequency distribution (SFD) is similar to models based on measured distributions at existing landing sites (e.g., Golombek and Rapp 1997;Golombek et al 2003bGolombek et al , 2008bGolombek et al , 2012b, then this translates to an overall rock-induced failure rate of ∼0.35 % in regions with a 5 % cumulative fractional area (CFA) and a failure rate of ∼2.5 % in regions with a 10 % CFA.…”
Section: Rock Abundancementioning
confidence: 99%
“…Results indicated that for the landing constraint of 10 % rock abundance, there should be multiple SEIS/WTS (3)(4)(5)(6)(7)(8)(9)(10)(11) and HP 3 (6-15) deployment sites that are free from 6 cm diameter (3 cm high) rocks. The second technique used Poisson statistics to evaluate the probability that a rock of a given diameter or larger would be present in a single random sample of a given area for a given rock abundance, which has been used to evaluate the probability of failure for landing MER, PHX and MSL in observed and modeled rock abundances (Golombek et al 2003b(Golombek et al , 2008b(Golombek et al , 2012b. The placement probabilities were determined for multiple discrete placement options for each instrument and WTS in the workspace and then made conditional on finding locations that are free from rocks >6 cm diameter for both instruments for a 10 % model rock abundance.…”
Section: Instrument Deploymentmentioning
confidence: 99%
“…5 for bulk density values of ρ = 1000 and 3000 kg m -3 , assuming c = 680 J kg -1 K -1 (Chesley et al 2003;Čapek, & Vokrouhlický, 2004); the density would be expected to increase with depth from the lower value, which is representative of porous surface material. Superimposed on the plot of , Golombek et al 2003 and references therein, for Martian rocks with diameter > 20 cm) are reached some tens of centimeters to meters below the surface in the case of the MBAs (the median diameter in our dataset = 24 km). In the case of the much smaller (km-sized) NEOs our results indicate that the porous surface layer is thinner, and suggest that large pieces of solid rock exist just a meter or less below the surface.…”
Section: Implications For Asteroid Regolith Structurementioning
confidence: 99%
“…Thermal inertia maps are often used to estimate rock or boulder populations (Golombek et al 2003). Prior to the descent and touchdown operation, it is important to assess whether the surface thermal environment and boulder distribution is hazardous for landing or not.…”
Section: Safe Operation For Descent Of Spacecraft To the Surfacementioning
confidence: 99%